Socio-Cognitive Perspectives in Business Venturing - Diego Zunino (Copenhagen Business School (CBS), 2018)
Entrepreneurship is an increasingly relevant and popular object of scholarly investigation. In this dissertation, I borrow relevant socio-cognitive constructs from the field of strategy and employ them to four relevant steps of the venture creation process. The purpose of this dissertation is to refine our understanding about perceptions in entrepreneurship through four essays. The first essay of the dissertation investigates entry into entrepreneurship. More specifically, I look at the relationship between institutional environment and predisposition to entrepreneurship as antecedents of entrepreneurial activity. The key insight is that, among other institutional factors, the perception of entrepreneurial activity positively moderates the role of innate predisposition to entrepreneurship. The second essay looks at the problem of resource acquisition when entrepreneurs have experienced business failure in the past. The key insight is that past failure is an ambiguous rather than a negative signal of entrepreneurial skill. When entrepreneurs provide additional information about their entrepreneurial skill, investors do not penalize past failure. The third essay addresses the problem of recruitment. The key insight is that startups can convey different types of information through their job advertisements and attract different types of early employees based on their level of human capital and risk propensity. The fourth essay looks at the step of technology product launch. The key insight is that perception of familiarity and creativity of category labels has an influence on their adoption to represent the technology product category. More precisely, I find that for both familiarity and creativity, there is an inverted U-shaped relationship associated to category labels' adoption. Through diverse theories and methodologies, the dissertation provides empirical support to the role perceptions play during the entrepreneurship process, and suggests rhetorical strategies entrepreneurs can exploit to gather resources and achieve competitive advantage.
hdl:10398/9638
Keywords: 650